Resource based View on Growth of Emerging Economies Multinationals: A Case Study of Tata Motors (Global Journal of Management and Business Research, 2021)
This study extends the resource-based view to explain the growth of an emerging market multinational firm. We have taken case of Tata motors due to its growth in various segment and internationalization in the various product markets. We have identified a process model of resource acquisition for internationalization of the firms. The process of the growth starts with internal capabilities development, innovation, and forming strategic alliances with the international partner followed by acquisition
Keywords: firm growth; internationalization; resource based view; emerging market; multinational firms